Detection of KRAS mutations in colorectal cancer by high-resolution melting analysis. Issue 10 (25th September 2009) - Ma, E S K; Wong, C L P; Law, F B F; Chan, W-K; Siu, D
Abstract : Aims: Mutation of the KRAS gene predicts the clinical response to the monoclonal antibody cetuximab in patients with advanced colorectal cancer (CRC). This study aimed to perform KRAS mutation detection on formalin-fixed paraffin-embedded (FFPE) tumour tissue by two different methods for comparison. Methods: The FFPE sample was microdissected to enrich for tumour cells. KRAS exon 2 mutations were performed on 100 Chinese patients with CRC by direct nucleotide sequencing and high-resolution melting (HRM) analysis. Results: KRAS exon 2 mutations were detected in a total of 62 patients with the two methods combined, comprising 11 different mutant alleles. Three common mutations p.Gly12Asp, p.Gly12Val and p.Gly13Asp accounted for approximately 70% of all cases. The concordant rate between the two methods was 95%. Four mutations not initially detected by direct sequencing were identified by HRM and confirmed by sequencing of the HRM amplicons. One mutation detected by direct sequencing was inadvertently grouped as a wild-type allele by HRM software, but this was readily rectified through manual review. Conclusion: HRM analysis is a sensitive method of detecting KRAS mutation on FFPE tumour tissue to guide cetuximab treatment and is applicable to routine molecular diagnostic service. Utilisation of HRM to screen for mutations upfront economises the resource used in the sequencing reaction.